(379) Model I. Investment Requirements Under A Given Time Shape Of Current Final Demand. النموذج الأول. متطلبات الاستثمار في فترة زمنية معينة: شكل الطلب النهائي الحالي - Frisch, Ragnar. (The Institute Of National Planning., 2018)
This study discusses a model of total domestic production (denoted as X) across various sectors of the economy over a time horizon defined by a plan with a fixed duration. The plan spans a number of years, with the origin of the time scale being the year t = 0 when the plan is decided. The study focuses on a fixed set of input coefficients for current account operations between different sectors of domestic production. Specifically, the input coefficient from sector h to sector k in year t determines the amount of input required. The assumption is that there are no substitution possibilities among inputs from different sectors. The model considers the execution of the plan over T years (e.g., T=5 years), and n sectors are involved. The approach assumes fixed, scale-independent input coefficients..